Kritik Sosial dalam Kumpulan Cerpen “Konvensi” karya A. Mustofa Bisri: Social Criticism in "Konvensi" Short Story Written by A. Mustofa Bisri - Nizar Halimatus Sadiyah; Ferdi Arifin (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This research studies contains social criticism in a collection of short stories titled "Konvensi" by A. Mustofa Bisri. This research is descriptive qualitative with social theories from Soerjono Soekanto and Budi Sulistyowati. Data collection is carried out by means of retrieval from documents and records. Data classification is done by categorizing the data found based on the types of social problems that are found. Data analysis was carried out with the stage of how to document the contents of the document. The results of this study indicate that in the collection of short stories "Konvensi" by A. Mustofa Bisri have found 9 types of social problems with 12 sections of problems. Each section is a reflection of the conditions of social problems that were being experienced by the community at the time the work was written.